Prebiotics in Dietary Management of Pediatric Gut Disease - Aljuaid, Hanouf khalid; Bosaeed, Bashayer Omar; Alghamdi , Ahmed Ali; Almanjoomi , Raid khalaf (Journal of Ecohumanism, 2024)
Prebiotics are substrates that host bacteria preferentially use to provide health benefits. Studies on prebiotics in children are scarcer than those on probiotics. Prebiotic-supplemented infant formula has been used in the majority of research, however there have been very few reports of employing add-on prebiotic supplements to prevent or cure gastrointestinal issues in children. The aim of this study was to evaluate effect of Prebiotics in Dietary management of pediatric Gut disease. This was a cross-sectional, case-control study using interviewer-administered questionnaires to survey prebiotic use in children with Gut disease. The Maternity and Children Hospital Makkah - Makkah Health Cluster was the recruitment site for participants. After attending outpatient clinic, 30 patients with gut disease and on prebiotics were questioned, while healthy controls were those who regularly attended clinics with gut disease and not on prebiotics. The findings emphasize the predominance of male participants and younger age groups, with gastrointestinal system issues being the most frequently reported medical condition. There were varied patterns of prebiotic use and participant experiences. Regarding the forms of prebiotics used, the majority of participants (66.7%) opted for syrups or drops. Participants also reported various side effects. The most common side effect was gas (46.7%). Regarding satisfaction with prebiotic use, 63.3% of participants expressed full satisfaction. We concluded that prebiotics are now acknowledged as a promising therapeutic tool for promoting general health and preventing and treating a variety of disease states in children. Indeed, the positive clinical use of prebiotics appears promising given the incredibly low risk of severe side effects, their ease of administration, and their potent ability to affect the makeup and function of the microbiota in the gut and beyond.